Comparative Studies of Chromen Derivatives by Using Numerical Methods - Mesli, Fouzia; Ghalem, Said (Asian Journal of Chemistry, 2017)
This study consists to develop program of molecular dynamics and to setup a method for calculations combined with ab initio (DFT and HF) to undertake theoretical investigations on products 4-hydroxy-chromen-2-one, 5,7-dihydroxy-4-methyl coumarin and 7-hydroxy-4-methyl coumarin. Studies were undertaken through a use of molecular program of dynamics for various both isothermal-isobaric NPT and canonical NVT of these products. It is showed that the classical approach gives good performances by means of simulation by molecular dynamics. Density functional theory calculations, B3LYP/6-31G, was performed for the determination of geometrical structure and vibrational assignment for the three systems. Full discussion of the framework vibrational modes was done using as criteria the study of the distorted geometric structures generated for each one of the vibrational modes in the low energy region. As results of this research we have obtained and characterized a novel 4-hydroxy-chromen-2-one, 5,7-dihydroxy-4-methyl coumarin, 7-hydroxy-4- methyl coumarin and we deduced the most probable structure using the experimental data of the infrared spectrum in conjunction with the theoretical DFT procedures. The calculated DFT spectra in the high and low energy regions agree well with the observed ones. The 4-hydroxy-chromen-2-one, 5,7-dihydroxy-4-methyl coumarin and 7-hydroxy-4-methyl coumarin were characterized by elemental analysis, IR, 1H NMR and mass spectrometry. It is hoped that this model with a intermolecular reaction could be an effective starting material for studying the properties of complex system in polar solvent and apolaire.